A new species of chimaera, Hydrolagus melanophasma sp. nov. (Chondrichthyes: Chimaeriformes: Chimaeridae), from the eastern North Pacific - James, Kelsey C.; Ebert, David A.; Long, Douglas J.; Didier, Dominique A. (Zootaxa, 2009)
A new species of chimaera, Hydrolagus melanophasma sp. nov. (Chimaeridae), is described from the eastern North Pacific. It is distinct from other eastern Pacific chimaeroids by the following characteristics: a large slightly curved dorsal fin spine extending beyond dorsal fin apex, a long second dorsal fin of uniform height throughout, large pectoral fins extending beyond the pelvic fin insertion when laid flat, trifid claspers forked for approximately one-quarter the total clasper length and a uniform black coloration throughout. The new species is compared to other eastern Pacific members of the genus Hydrolagus including H. alphus, H. colliei, H. macrophthalmus, and H. mccoskeri. Remote Operated Vehicle (ROV) video footage has identified and documented Hydrolagus melanophasma from the Gulf of California. ROV observations suggest that individuals typically occur over soft-bottom habitats or cobble patches with minimal vertical relief. This is in contrast to other eastern Pacific Hydrolagus species that tend to occur in areas of high rocky relief. The known distribution of this new species at present extends from southern California, U.S.A., along the Pacific coast of Baja California, Mexico, and into the Gulf of California.